Organizational Culture Dynamics and Work Motivation in Improving Employee Performance at PT. Telkom Indonesia - Putri, Yuli Anika; Samtani, Rachel Dwi; Wahjono, Sentot Imam (Golden Ratio of Data in Summary, 2025)
This study aims to analyze how PT Telkom Indonesia's organizational culture and work motivation affect employee performance. A literature study using a descriptive qualitative approach found that applying corporate values and implementing a performance and welfare-based work motivation system have significantly increased employee loyalty and productivity through cultural transformation. A structured competency and performance evaluation system based on the Individual Performance System (IPS) also improves the achievement of organizational goals. By combining these three components, beneficial synergies were created that helped the digital transformation of the business succeed and provide a long-term competitive advantage. The results of this study highlight the importance of a comprehensive approach to HR management to meet the changing demands of the telecommunications sector.